Psychological Endurance and its Relation to Some Personal Traits Students of the Institute of Applied Arts (Journal of the College of Education for Women, 2019)
Cognitive methods play the role of regulator of the human environment for its direct relationship with sensory stimuli and stimuli associated with the organization of information and ideas and their preparation for use in subsequent situations. These methods determine the characteristic or ideal way of individual personality in the differentiation and integration of attitudes or cognitive field to which he is exposed. Therefore, the research aimed at the level of psychological stress and its relation to some personal characteristics that show the personality of the artist or the students of art.Current research aims to.Identifying the extent of psychological stress and its relation to the personal characteristics of students of the Institute of Applied Arts / Middle Technical University.Identify the psychological endurance of students of the Institute of Applied Arts / / Middle Technical UniversityIdentifying the relationship between psychological endurance and some personal characteristics among the students enrolled in the Institute of Applied Arts / / Middle Technical University.Keywords: Psychological Endurance, Personal Traits